Converting grassland to wildflower meadow: impact on soil quality indicators for carbon sequestration - Alice A. Breeveld; Saskia Pagella; Jane Fisher (Academia Environmental Sciences and Sustainability)
The extensive loss of carbon-rich, species-rich grasslands to agriculture and development has had detrimental impacts on wildflower abundance and diversity. Therefore, conversion of verges, lawns, and fields into wildflower meadows (WFMs) has gained prominence in recent years. However, a frequent recommendation for WFM establishment is to reduce soil fertility, raising concerns regarding the impact on carbon sequestration. To address the question of how WFM conversion might affect soil carbon retention, an experiment was conducted in Surrey, UK, converting grassland into WFM using different strategies: deturfing or scarifying, plus seed sowing. Measurements included earthworm abundance, live biomass, and microbial decomposition rates via a cotton strip assay (CSA), to provide insights into the initial phase of carbon sequestration: organic matter decomposition. The findings unveiled critical insights. In the short term, WFM conversion resulted in reduced earthworm populations relative to the control, especially when the conversion involved a high level of disturbance by removing turf. Conversely, mowing led to increased earthworm populations and accelerated CSA decomposition compared to the control. These findings suggest that the effects of disturbance and removal of biomass through deturfing or scarifying, and the energy supply provided by mowing and leaving the arisings, had more impact on the earthworm population and CSA decomposition than the increased diversity of the sown wildflowers. Successful WFM establishment can be achieved without turf removal, a practice that exerts adverse effects on soil life. These findings have broader implications for grassland resource management in the context of climate change mitigation through soil carbon storage.